Hepatic Arterial Infusion Chemotherapy versus Sorafenib in Patients with Advanced Hepatocellular Carcinoma - Ueshima, Kazuomi (Liver Cancer, 2020)
BACKGROUND: Prior to the approval of sorafenib, hepatic arterial infusion chemotherapy (HAIC) was offered to patients with advanced hepatocellular carcinoma (HCC) in East Asia, particularly Japan. According to the Japanese guidelines, HAIC is recommended as one of the treatment options in patients without extrahepatic metastasis (EHM). METHODS: The present cohort study compared the use of HAIC and sorafenib on outcomes of patients with advanced HCC. Consecutive patients with advanced HCC who received HAIC or sorafenib as a first-line systemic therapy were enrolled from 10 Japanese institutions. The primary outcomes were overall survival (OS) in patients with macrovascular invasion (MVI), but without EHM, and OS in patients without both MVI and EHM. RESULTS: Between 2009 and 2016, 2,006 patients were enrolled (541 HAIC patients, 1,465 sorafenib patients). After propensity score matching, the OS of patients with MVI but without EHM was significantly longer in the HAIC group compared with the sorafenib group (10.1 vs. 9.1 months for the HAIC and sorafenib groups, respectively; n = 170 for each group; hazard ratio [HR] 0.668; 95% confidence interval [95% CI] 0.475–0.935; p = 0.018). There was no significant difference in OS between patients without both MVI and EHM (12.2 vs. 15.4 months for the HAIC and sorafenib groups, respectively; n = 76 in each cohort after propensity score matching; HR 1.227; 95% CI 0.699–2.155; p = 0.475). CONCLUSION: HAIC is a potential front-line treatment choice in a subpopulation of patients with advanced HCC with MVI but without EHM.